1980
DOI: 10.1113/jphysiol.1980.sp013244
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen depletion of bag1 fibers elicited by stimulation of static gamma axons in cat peroneus brevis muscle spindles.

Abstract: 1. The distribution of static fusimotor axons to intrafusal muscle fibres in cat peroneus brevis spindles has been studied with the glycogen depletion method. 2. In each of six experiments three to seven static axons were stimulated. The muscle was subsequently quick-frozen and cut in serial transverse sections that were stained for glycogen. In each muscle, nearly all the spindles were examined for depletion. 3. Intrafusal muscle fibres displaying zones of complete glycogen depletion were observed in fifty-tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The activated muscle fibres then stand out from the rest by virtue of having been depleted of their normal glycogen stores. On applying this technique to the spindle it has been repeatedly shown that stimulation of static axons may deplete bag fibres as well as chain fibres, whereas on activation of dynamic axons the depletion is restricted to bag fibres (Brown & Butler, 1973, 1975 Emonet-Denand, Harker, Jami & Laporte, 1976;Emonet-Denand, Jami, Laporte & Tankov, 1980). (c) Intracellular recording.…”
mentioning
confidence: 99%
“…The activated muscle fibres then stand out from the rest by virtue of having been depleted of their normal glycogen stores. On applying this technique to the spindle it has been repeatedly shown that stimulation of static axons may deplete bag fibres as well as chain fibres, whereas on activation of dynamic axons the depletion is restricted to bag fibres (Brown & Butler, 1973, 1975 Emonet-Denand, Harker, Jami & Laporte, 1976;Emonet-Denand, Jami, Laporte & Tankov, 1980). (c) Intracellular recording.…”
mentioning
confidence: 99%
“…In conclusion, the view based on glycogen depletion observations Emonet-Denand et al 1980;Jami et al 1980) that static y-axons substantially participate in bag, innervation should now be abandoned since our present work strongly suggests that in 'fatigued' spindles (i.e. spindles in which the sensory ending responses to y stimulation have become very weak) non-neural depletion of bag, fibres occurs.…”
Section: Discussionmentioning
confidence: 57%
“…The non-neural factor is unlikely to be the stretch-induced contraction of bag1 fibres described by Poppele & Quick (1981), as proposed by Barker & Banks (1984), for two reasons: first, because in experiments A and B the chain and bag2 fibres that were activated for 5 and 9 h, respectively, had been given ample opportunity (if bag, stretching really occurs) to stretch neighbouring bag, fibres; however, only one bag, pole out of nineteen was depleted; secondly, because it is known that small amplitude vibrations applied to muscles in order to mimic possible stretch of bag, fibres by the contraction-relaxation of other intrafusal muscle fibres does not change the glycogen content of bag1 fibres (Emonet-Denand et al 1980). However, there is current evidence that large stretches can change the Ia responses to subsequent dynamic y stimulation (Emonet-Denand, Hunt & Laporte, 1983) and also elicit extensive glycogen depletion in bag1 fibres (L. Decorte, F. Emonet-Denand & Y.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a controversy has arisen as to whether motor axons which have a static action on spindle afferent discharge may ever terminate on the bag, fiber. On this subject, discrepancy exists between observations made with the glycogen-depletion method (Brown and Butler, 1973;Barker et al, 197613;Emonet-Denand et al, 1980) and cinematographical studies of living muscle spindles (Bessou and Pages, 1975;Boyd, 1976a;Boyd et al, 1977Boyd et al, , 1979. None of these studies has dealt with quantitative aspects of bag, fiber motor innervation.…”
mentioning
confidence: 97%